P2X7 Receptor Function in Bone-Related Cancer - Elena Adinolfi; Francesca Amoroso; Anna Lisa Giuliani (Journal of Osteoporosis)
Modulation of tumor microenvironment by different mediators is central in determining neoplastic formation and progression. Among these molecules extracellular ATP is emerging as a good candidate in promoting cell growth, neovascularization, tumor-host interactions, and metastatization. This paper summarizes recent findings on expression and function of P2X7 receptor for extracellular ATP in primary and metastatic bone cancers. Search of mRNA expression microchip databases and literature analysis demonstrate a high expression of P2X7 in primary bone tumors as well as in other malignancies such as multiple myeloma, neuroblastoma, breast, and prostate cancer. Evidence that P2X7 triggers NFATc1, PI3K/Akt, ROCK, and VEGF pathways in osteoblasts promoting either primary tumor development or osteoblastic lesions is also reported. Moreover, P2X7 receptor is involved in osteoclast differentiation, RANKL expression, matrix metalloproteases and cathepsin secretion thus promoting bone resorption and osteolytic lesions. Taken together these data point to a pivotal role for the P2X7 receptor in bone cancer biology.